Hubungan Pengetahuan Penggunaan Mobile JKN Untuk Pendaftaran Periksa Kesehatan Dengan Kepuasan Pengguna - Wahyu Nastien; Caecilia Titin Retnani; Eka Ratnawati (Jurnal Kesehatan, 2025)
JKN Mobile application is a digital innovation created by BPJS to facilitate health services, including examination registration. One hospital in Temanggung found that patients have not utilized the JKN Mobile application optimally, which has an impact on satisfaction with health services. This study aims to determine the relationship between knowledge of using the JKN Mobile application for health check registration and user satisfaction in the hospital. This study is a quantitative, observational-analytical survey, using a cross-sectional approach. The sample comprised 110 respondents, selected purposively from visitors at the hospital who are JKN participants and have used the JKN Mobile application. The data collection instrument was a questionnaire that had been tested for validity and reliability. The results showed a significant relationship between knowledge of using the JKN Mobile application and user satisfaction (p = 0.000; p < 0.05). The percentage of users with knowledge was mainly in the good category (91.8%), totalling 101 people. Meanwhile, 102 users were categorized as satisfied (92.7%). These results indicate that the better users' knowledge of how to use the Mobile JKN application, the higher their satisfaction with accessing it. Therefore, it is recommended that users be more active in learning to use the application, particularly the check-up registration feature.